From Anxiety to Hardiness: The Role of Self-Efficacy in Spanish CCU Nurses in the COVID-19 Pandemic - Fernanda Gil-Almagro; Fernando José García-Hedrera; Francisco Javier Carmona-Monge; Cecilia Peñacoba-Puente (Medicina, 2024)
Background and Objectives: Evidence shows that throughout the COVID-19 pandemic, nurses suffered from emotional symptoms, yet in spite of this, few studies within “positive psychology” have analyzed the emergence/promotion of positive traits, such as hardiness. In this context, the present study aimed to test a model regarding the mediating role of self-efficacy between anxiety experienced at the beginning of the COVID-19 pandemic and hardiness assessed six months later among nurses in critical care units (CCU) in Spain. Materials and Methods: An observational, descriptive, prospective longitudinal study with two data collection periods: (1) from the 1 to the 21 June 2020 (final phase of the state of alarm declared in Spain on 14 March) in which socio-demographic and occupational variables, anxiety (Depression, Anxiety and Stress Scale, DASS-21), self-efficacy (General Self-Efficacy Scale, GSES) and basal resilience (Resilience Scale-14, RS-14) were assessed, and (2) a follow-up 6 months later (January–March 2021) in which hardiness (Occupational Hardiness Questionnaire, OHQ) was evaluated. To analyze the data, multivariate regressions were performed using the PROCESS macro (simple mediation, model 4). Results: A total of 131 Spanish nurses from CCUs, with a mean age of 40.54 years (88.5% women) participated in the study. Moderate and severe levels of anxiety were observed in 19.1% of the sample. Significant and positive correlations were observed between self-efficacy, hardiness and resilience (all p < 0.001). Significant negative correlations were observed between anxiety and self-efficacy (p < 0.001), hardiness (p = 0.027) and resilience (p = 0.005). The indirect effect of anxiety on hardiness through self-efficacy was significant (Effect (SE) = −0.275 (0.100); LLCI = −0.487, ULCI = −0.097), contributing to 28% of the variance, including resilience (p = 0.015), age (p = 0.784), gender (p = 0.294) and years of experience (p = 0.652) as covariates. A total mediation was observed (non-significant anxiety-hardiness direct effect; Effect (SE) = −0.053 (0.215), t = 0.248, p = 0.804, LLCI = −0.372, ULCI = 0.479). Conclusions: The results suggest that in Spanish CCU nurses, anxiety experienced at the beginning of the COVID-19 pandemic may contribute to the development of hardiness through positive resources such as self-efficacy.